SUSTAINABLE DEVELOPMENT OF FUEL AND ENERGY ENTERPRISES: MODELING BUSINESS PROCESSES OF HUMAN CAPITAL MANAGEMENT - Kuzmin, Yevgeniy; Guseva, Valentina (THE INNOVATION ECONOMY, 2024)
Abstract. The article is devoted to the analysis of the role of human capital in the sustainable development of the fuel and energy complex (FEC) and considers the soft systems methodology (SSM) as a tool for dynamic modeling of management processes. As part of the work, a review of the literature on the topic of sustainable development of the fuel and energy complex and the role of human capital in this process was carried out, and various approaches to understanding the essence and nature of human capital were considered. The authors analyze studies demonstrating the multifaceted influence of human capital on sustainable development, and emphasize the importance of its study and management in the context of the fuel and energy complex. The article proposes a conceptual model illustrating the interconnected business processes of human capital management. The model includes analysis and optimization of business processes, ranging from determining personnel needs to managing the exit of employees from the company. The key stages of personnel development are described. Particular attention is paid to the dynamic nature of these processes and their impact on the sustainable development of fuel and energy enterprises. The authors emphasize the importance of an integrated approach to human capital management, which should take into account both formal and informal aspects.